Synthesis, mechanism of action, and structure-activity relationships of 1,3-oxazolidinones as anti-bacterial Agent: A review - Ali Hantosh; Nawal Rajab; Faris Abachi (University of Mosul, 2022)
Background: 1,3-oxazolidinones are an important class of antibiotics that are recognized with higher activities against Gram-positive bacteria. linezolid, tedizolid phosphate, and radezolid are important examples of this group. Aim: The aim of this review is to study the effect of 1,3-oxazolidinone derivatives as Gram-positive antibacterial agents. Results: There are many methods for preparing the oxazolidinone derivatives. Many patents Three new antibacterial oxazolidinones are linezolid, tedizolid phosphate, and radezolid. They differ in the side chain according to their structure-activity relationship. Conclusion: Study the structure-activity relationship (SAR) of oxazolidinone derivatives as new antibacterial agents.